Regímenes laborales y su incidencia en el desempeño laboral de los servidores de la Universidad Nacional de Trujillo - sede central 2017 - Rodriguez Galarreta, Miguel Angel (2019)
ABSTRACT The present investigation was oriented to determine the Labor Regimes and their incidence in the Labor Performance of the servants of the National University of Trujillo - Headquarters 2017, the same one that was realized through a study and analysis of the variables Labor Regimes and Performance Labor, the main objective of the research was to determine how labor regimes affect the performance of the servers of the National University of Trujillo - Headquarters 2017, the survey was applied as an instrument of data collection, the population was conformed by 190 servers, obtaining a representative sample equal to 127 servers, a survey questionnaire was applied to the sample obtained, in order to study the variables and the incidence between independent and dependent; the data collection instruments were validated by the Alpha method of Cronbach, yielding an Alpha of 0.753 for the variable Labor Regimes and 0.758 for the variable Labor Performance; We reviewed previous research studies related to the subject investigated, in the same way the theories were oriented to the dimensions of both variables, the type of research is non-experimental, transversal and correlational, reaching the conclusion after processing the variables, which does not there is significant evidence to reject the null hypothesis since P> 0.05, therefore there is no significant relationship between the variables Work Regime and Work Performance at a confidence level of 95%. This fact allowed us to recommend necessary tactical actions, aimed at strengthening those factors that have deficiencies to exercise a change that maximizes the acquisition of better knowledge, skills and attitudes in the servers, in order to make the server more efficient, efficient and productive; in order to achieve the institutional objectives.